Manganese-based fiber catalytic material as well as preparation method and application thereof

By pre-oxidizing acrylic fibers and in-situ oxidizing potassium permanganate, combined with ozone in-situ activation treatment, the prepared manganese-based fiber catalytic material solves the problem of insufficient thermal oxidation and catalytic activity of the catalyst, significantly improving the catalytic performance and Thermal stability.

CN119425809AActive Publication Date: 2025-02-14HENAN ACADEMY OF SCI CHEM RES INST CO LTD +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411373395.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-12-11
Filing Date
2024-09-29
Publication Date
2025-02-14
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

The existing organic fiber catalysts have insufficient thermal oxidation resistance and catalytic activity during catalyzing ozone oxidation reaction, resulting in a significant reduction in catalytic performance.

Method used

By pre-oxidizing acrylic fibers and in-situ oxidizing potassium permanganate, a manganese-based polymer fiber catalytic material precursor was prepared, and ozone was used to perform ozone activation treatment using ozone gas stream, peeling off organic fragments covered with fiber surfaces, and exposing catalytic activity loci.

Benefits of technology

The catalytic performance and thermal stability of manganese-based fiber catalytic materials are significantly improved, the exposure of catalytic active sites is enhanced, and the removal rate of pollutants such as toluene is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005068133770000011
    Figure HDA0005068133770000011
  • Figure HDA0005068133770000012
    Figure HDA0005068133770000012
  • Figure HDA0005068133770000021
    Figure HDA0005068133770000021
Patent Text Reader

Abstract

The invention belongs to the technical field of new materials, and discloses a manganese-based fiber catalytic material preparation method, which specifically comprises: carrying out pre-oxidation treatment on a polymer fiber to obtain a pre-oxidized polymer fiber; carrying out in-situ oxidation on the pre-oxidized polymer fiber by adopting a potassium permanganate in-situ oxidation method to obtain a manganese-based polymer fiber catalytic material precursor; and carrying out ozone in-situ activation treatment on the manganese-based polymer fiber catalytic material precursor by adopting ozone airflow to obtain the manganese-based fiber catalytic material. The prepared manganese-based fiber catalytic material is stable in oxidation resistance, high in heat stability, excellent in catalytic performance and mild in preparation condition, in addition, the selection of forms is not limited, the manganese-based fiber catalytic material can be applied in any forms such as disordered fibers, woolen yarns, needle-punched fabrics and knitted fabrics, filling is convenient, and the use depth and range of the catalytic material are greatly widened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of new materials, and specifically relates to a manganese-based fiber catalytic material and a preparation method and application thereof. Background Art

[0002] In recent years, research in the field of functionalizing common textile fibers (synthetic and natural fibers) to keep the original characteristics and advantages of the fibers while also having various special properties and uses has attracted increasing attention. Textile fibers are in sufficient supply, of various varieties, and at reasonable prices, and are a good source of raw materials for obtaining new materials. Chemical modification is an important means of functionalizing fibers. The active chemical groups carried by the fibers react chemically with certain molecules or ions, or react chemically with the assistance of ultrasound, microwaves, or heat, so that the fibers have new surface chemical properties, thereby having new functions such as antistatic, water absorption and moisture retention, adsorption and separation, antibacterial deodorization, and catalysis. Chemical modification can be achieved using different fibers as raw materials through different treatment methods and processes. At present, most of the supported metal oxide catalysts are based on porous materials such as metal oxides or molecular sieves. Although the catalysts prepared with these substrate materials have excellent stability and dispersibility, their morphology is not easy to change, and they are difficult to fill and replace in industrial applications. In addition, most of the active sites of molecular sieve or metal oxide-based catalysts are located inside the particles. In the actual reaction process, the internal diffusion process has a greater impact on the catalytic performance. At the same time, the intermediate product particles generated by the reaction are easily deposited in the catalyst pores to block them, thereby reducing the activity of the catalyst. Studies have shown that the rich acid-base microenvironment on the catalyst surface is of great significance for improving the catalytic performance of the catalyst. Nevertheless, due to the participation of organic polymer fibers, the active sites of the prepared catalyst will be more or less covered by organic fragments or inactive components, but they cannot be activated by high-temperature oxidation like inorganic carriers, resulting in fewer active sites on the prepared fiber surface and serious coverage by organic fragments, resulting in significantly lower catalytic activity than similar inorganic carrier catalysts. In addition, the literature "Duan W, Tang K, Zhao L, et al. MnO xNanoparticle-loaded polyacrylonitrile fibers for efficient catalyticozonation of toluene[J]. Atmospheric Pollution Research, 2024, 15 (5):102079” The study showed that the polymer fiber carrier was degraded during the ozone oxidation degradation of toluene using polymer fibers loaded with manganese oxide. Therefore, for organic fiber catalysts, when they are used to catalyze ozone oxidation reactions, their thermal oxidation resistance and catalytic activity need to be further improved. Summary of the invention

[0003] In view of the problems and shortcomings in the prior art, the purpose of the present invention is to provide a manganese-based fiber catalytic material and a preparation method and application thereof.

[0004] To achieve the purpose of the invention, the technical solution adopted by the present invention is as follows: The first aspect of the present invention provides a method for preparing a manganese-based fiber catalytic material, which comprises: pre-oxidizing polymer fibers to obtain pre-oxidized polymer fibers; in-situ oxidizing the pre-oxidized polymer fibers using a potassium permanganate in-situ oxidation method to obtain a manganese-based polymer fiber catalytic material precursor; and in-situ activating the manganese-based polymer fiber catalytic material precursor using an ozone gas flow to obtain a manganese-based fiber catalytic material.

[0005] According to the above preparation method, preferably, the temperature of the ozone in-situ activation treatment is 110-130°C, and the time is 2-8 hours. More preferably, the temperature of the ozone in-situ activation treatment is 110-120°C, and the time is 2-6 hours.

[0006] According to the above preparation method, preferably, the concentration of ozone in the ozone gas flow during the ozone in-situ activation treatment is 10 to 40 mg / L. More preferably, the concentration of ozone in the ozone gas flow is 10 to 30 mg / L.

[0007] According to the above preparation method, preferably, the mass space velocity of the ozone gas flow during the ozone in-situ activation treatment is 240000-1200000 mL / (g·h). More preferably, the mass space velocity of the ozone gas flow during the ozone in-situ activation treatment is 480000-1200000 mL / (g·h).

[0008] According to the above-mentioned preparation method, preferably, the specific operation of in-situ oxidation of the pre-oxidized polymer fiber by potassium permanganate in-situ oxidation method is: adding the pre-oxidized polymer fiber into potassium permanganate solution for oxidation reaction, collecting the polymer fiber after the reaction is completed, and washing and drying the polymer fiber to obtain a manganese-based polymer fiber catalytic material precursor.

[0009] According to the above preparation method, preferably, the concentration of the potassium permanganate solution is 20-100 mmol / L, and the liquid-to-solid ratio of the potassium permanganate solution to the pre-oxidized polymer fiber is (20-200) mL:1 g (i.e., 20 mL-200 mL of potassium permanganate solution is added to every 1 g of pre-oxidized polymer fiber for pre-oxidation reaction).

[0010] According to the above preparation method, preferably, the temperature of the oxidation reaction is 10-40° C., and the time of the oxidation reaction is 0.5-12 h.

[0011] According to the above preparation method, preferably, the pre-oxidation treatment is specifically: heat-treating the polymer fiber in an oxygen-containing gas.

[0012] According to the above preparation method, preferably, the temperature of the heat treatment is 200-250° C., the time of the heat treatment is 0.5-4 h; and the flow rate of the oxygen-containing gas is 100-500 mL / min.

[0013] According to the above preparation method, preferably, the pre-oxidation treatment is: placing the polymer fiber in an oxygen-containing gas, heating it to 200-250°C, and heat-treating it for 0.5-4 hours. More preferably, the heating rate of the heating is 2-20°C / min.

[0014] According to the above preparation method, preferably, the polymer fiber is acrylic fiber or modified acrylic fiber.

[0015] According to the above preparation method, preferably, the modified acrylic fiber is an acrylic fiber grafted with amino groups, and the amino groups are grafted onto the acrylic fiber by reacting a polyamine compound with a -CN group in the acrylic fiber.

[0016] According to the above preparation method, preferably, the preparation method of the acrylic fiber grafted with amino groups is: adding the acrylic fiber to a polyamine compound solution for swelling treatment, reacting at 100-150°C for 1-12 hours after swelling, cooling, washing, and drying after the reaction to obtain the acrylic fiber grafted with amino groups. More preferably, the swelling treatment temperature is 60-80°C, and the swelling treatment time is 4-12 hours.

[0017] According to the above preparation method, preferably, the polyamine compound is one or more of ethylenediamine, diethylenetriamine, triethylenetetramine and polyethylenepolyamine.

[0018] According to the above preparation method, preferably, the dosage of the polyamine compound solution is: 20ml-200ml of the polyamine compound solution is added to every 1g of acrylic fiber for swelling treatment, and the mass fraction of the polyamine compound in the polyamine compound solution is 5-100%.

[0019] According to the above preparation method, preferably, the solvent of the polyamine compound solution is at least one of water, ethylene glycol, propylene glycol and glycerol.

[0020] According to the above preparation method, preferably, the amino group includes a primary amino group and / or a secondary amino group. More preferably, the nitrogen heterocycle is produced by cyclization of one or more of a cyano group, a carbonyl group and an amino group.

[0021] The second aspect of the present invention provides a manganese-based fiber catalytic material prepared using the preparation method described in the first aspect.

[0022] According to the above-mentioned manganese-based fiber catalytic material, preferably, the manganese-based fiber catalytic material is in the form of one or more of fiber, wool, needle-punched cloth, and knitted cloth.

[0023] The third aspect of the present invention provides the use of the manganese-based fiber catalytic material described in the second aspect in a catalyst.

[0024] According to the above application, preferably, the catalyst includes a catalyst in an ozone oxidation process; more preferably, the ozone oxidation includes ozone oxidation degradation of benzene series in a gas phase; the benzene series includes toluene and / or benzene; and the degradation temperature is 70-110°C.

[0025] Compared with the prior art, the present invention has the following positive and beneficial effects: (1) Due to the participation of organic polymer fibers, the active sites of the prepared catalyst will be more or less covered by organic fragments or inactive components, but it cannot be activated by high-temperature oxidation like an inorganic carrier, resulting in fewer active sites on the surface of the prepared fiber and serious coverage by organic fragments, resulting in its catalytic activity being significantly lower than that of similar inorganic carrier catalysts; the present invention uses acrylic fiber as a matrix material, and grafts rich amine functional groups on the surface of acrylic fiber by a chemical grafting method to prepare amino fiber (i.e., acrylic fiber grafted with amino groups), and then places the amino fiber in an air atmosphere for pre-oxidation at a high temperature to obtain pre-oxidized amino fiber, and the pre-oxidized amino fiber is subjected to an in-situ oxidation method with potassium permanganate to obtain A manganese-based polymer fiber catalyst material precursor is prepared, and then an ozone gas flow is used to perform an ozone in-situ activation treatment on the manganese-based polymer fiber catalyst material precursor. During the ozone in-situ activation treatment, based on the catalytic activity of part of the manganese oxide on the fiber surface, the organic fragments covering the surface of the catalytic active sites are stripped and degraded through self-catalytic ozone oxidation, resulting in an increase in the number of exposed manganese oxide catalytic active sites on the surface of the polymer fiber catalyst material, thereby improving the catalytic performance of the polymer fiber catalyst material, and effectively solving the problem of low activity or inactivation of the catalytic material due to the covering of the catalytic active sites on the surface of the manganese-based polymer fiber catalyst material; at the same time, the thermal stability of the manganese-based polymer fiber catalyst material can be further improved during the ozone in-situ activation treatment.

[0026] (2) The manganese-based fiber catalytic material prepared by the present invention can be used to catalyze the ozone oxidation degradation of pollutants, such as volatile organic compounds, odor pollutants, etc., and when the manganese-based fiber catalytic material of the present invention is used to degrade polluted gas with a toluene concentration of 100 ppm under the conditions of an air velocity of 120,000 mL / (g·h), a reaction temperature of 90°C, and an ozone concentration of 4.0-4.5 mg / L, the toluene removal rate reaches 99.2% to 100%, and the selectivity of inorganic carbon oxides (carbon monoxide and carbon dioxide) in the product is greater than 99%; under the same degradation conditions, the toluene removal rate is only 65% ​​to 83% when the manganese-based polymer fiber material precursor that has not been activated by ozone is used as a catalyst; therefore, compared with the process without in-situ ozone activation, the catalytic activity of the manganese-based fiber catalytic material prepared by the present invention is significantly improved.

[0027] (3) The present invention heat treats the polymer fiber in an oxygen-containing gas, which can cause some functional groups on the fiber surface to undergo cross-linking and cyclization, thereby improving the thermal stability and oxidation resistance of the polymer fiber catalytic material and solving the problems of poor thermal stability and poor oxidation resistance of the manganese-based polymer fiber catalytic material.

[0028] (4) The manganese-based fiber catalytic material prepared by the present invention has stable oxidation resistance, high thermal stability and excellent catalytic performance. In addition, there is no restriction on the choice of form, and it can be used in any form such as random fibers, wool yarn, needle-punched cloth, knitted cloth, etc., which is not only convenient for filling, but also greatly broadens the depth and breadth of the use of the catalytic material.

[0029] (5) The preparation method of the manganese-based fiber catalytic material of the present invention is simple to operate, requires mild conditions, and can be promoted and applied industrially. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The SEM characterization images of the manganese-based fiber catalytic material and the manganese-based fiber catalytic material precursor prepared in Example 1 of the present invention; wherein a1-a3 are the morphology images of the manganese-based fiber catalytic material precursor at different microscopic scales, and b1-b3 are the morphology images of the manganese-based fiber catalytic material at different microscopic scales; Figure 2 This is an EDS surface scan result diagram of the preparation of the manganese-based fiber catalytic material in Example 1 of the present invention; wherein a1-a2 is a surface scan diagram of the Mn element on the surface of the manganese-based fiber catalytic material precursor, and b1-b2 is a surface scan diagram of the Mn element on the surface of the manganese-based fiber catalytic material; Figure 3 Thermogravimetric analysis diagrams of fibers at various preparation stages during the preparation of the manganese-based fiber catalytic material in Example 1 of the present invention; Figure 4 This is a graph showing the test results of the effect of ozone activation time on the catalytic performance of manganese-based fiber materials. DETAILED DESCRIPTION

[0031] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.

[0032] The following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0033] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. In addition, it should also be understood that when the terms "comprise" and / or "include" are used in this specification, it indicates that there are features, steps, operations, parts and / or combinations thereof.

[0034] The experimental methods in the following examples without specifying specific conditions all adopt conventional techniques in the art or follow the conditions recommended by the manufacturers; the reagents or instruments used without specifying the manufacturers are all conventional products that can be obtained commercially.

[0035] Embodiment 1: A method for preparing a manganese-based fiber catalytic material, specifically comprising: The commercial acrylic fiber was washed three times with deionized water and dried at 60°C to constant weight. 200 mL of triethylenetetramine was added to a three-necked flask, and then 2 g of pretreated acrylic fiber was weighed and immersed in triethylenetetramine to swell at 60°C for 12 hours, then heated to 150°C for 3 hours, cooled, washed, and dried at 60°C to constant weight to obtain amino fiber, and its exchange capacity was measured to be 5.93 mmol / g; 1 g of the obtained amino fiber was placed in a tubular furnace, and air was passed into the tubular furnace at 200 mL / min for 30 minutes of equilibrium, then heated to 200°C at 10°C / min and kept at a constant temperature for 4 hours, cooled, and sealed for storage , to obtain pre-oxidized amine-based fiber; 0.5g of pre-oxidized amine-based fiber was placed in a conical flask containing 20mL of 100mmol / L potassium permanganate solution, and the reaction was carried out at 40℃ for 0.5h, and then the fiber was taken out, washed with water until the eluate was colorless, and dried at 60℃ to constant weight to obtain a manganese-based fiber catalytic material precursor; the manganese-based fiber catalytic material precursor was placed in an ozone gas flow with an ozone concentration of 20mg / L, a mass space velocity of 1200000mL / (g·h), and a temperature of 110℃ for in-situ activation for 4h to obtain a manganese-based fiber catalytic material. After testing, the manganese content in the manganese-based fiber catalytic material was 255.4 mg / g.

[0036] The manganese-based fiber catalytic material and the manganese-based fiber catalytic material precursor prepared in this embodiment were used to catalyze the ozone oxidation degradation of toluene in the gas; the degradation experimental conditions were: space velocity 120000 mL / (g·h), reaction temperature 90°C, toluene concentration in the gas 100 ppm, ozone concentration 4.0-4.5 mg / L, and gas humidity 0-10%. After the degradation reaction was completed, the toluene content in the gas was detected and the toluene removal rate was calculated.

[0037] It was found through testing that the manganese-based fiber catalytic material prepared in this embodiment has a removal rate of 100% for toluene in the gas, and the selectivity of inorganic carbon oxides in the product is greater than 99%; while the removal rate of toluene in the gas by the manganese-based fiber catalytic material precursor is 83%. This shows that the catalytic performance of the manganese-based fiber catalytic material prepared in the present invention is significantly higher than that of the manganese-based fiber catalytic material precursor that has not been treated with ozone in-situ activation, and can be used to catalyze ozone oxidation to degrade toluene pollutants in the gas.

[0038] The manganese-based fiber catalytic material and the manganese-based fiber catalytic material precursor prepared in this example were characterized by SEM. Figure 1 shown.

[0039] Depend on Figure 1It can be seen that after ozone activation, the fibers become thinner, the manganese oxide nanoparticles on the surface become clearer, and a large number of pores are generated. This shows that the strong oxidizing property of high-concentration ozone and the strong catalytic effect of manganese oxide species on the fiber surface cause the organic matter fragments covering the surface of the manganese oxide active species of the fiber catalyst to be oxidized and peeled off, leaving the manganese oxide active species exposed on the fiber surface. There is a certain degree of accumulation and agglomeration between adjacent nanoparticles on the fiber catalyst surface, and no obvious boundary is observed between the nanoparticles and the fiber matrix, indicating that the manganese oxide particles MnO x The fibers are connected by chemical bonds, and the stacks of manganese oxide nanoparticles are bound together by van der Waals forces.

[0040] The manganese-based fiber catalytic material prepared in this example was subjected to EDS surface scanning. The EDS surface scanning results are as follows: Figure 2 shown.

[0041] Depend on Figure 2 It can be seen that the manganese species on the surface of the manganese-based fiber catalyst material prepared by the present invention are evenly dispersed, which confirms that the manganese oxide active species are evenly dispersed on the fiber surface with the assistance of functional groups, and also confirms that the prepared fiber catalyst material is a manganese-based catalyst. The density of manganese elements on the surface of the fiber catalyst increases significantly after ozone activation, which shows that the ozone activation process can effectively strip off the organic fragments covering the surface of the manganese oxide active species, increase the effective active species exposed on the fiber surface, and thus significantly improve its catalytic activity.

[0042] Thermogravimetric analysis was performed on the fibers at each stage in the preparation process of the manganese-based fiber catalyst material of this embodiment, wherein the fibers at each stage include amine-based fibers (abbreviated as APANF), pre-oxidized amine-based fibers (abbreviated as TAPANF), manganese-based fiber catalyst material precursor (abbreviated as MnO x / TAPANF) and manganese-based fiber catalytic materials (abbreviated as oo -MnO x / TAPANF). Thermogravimetric analysis results are shown in Figure 3 shown.

[0043] Figure 3 This is a thermogravimetric analysis diagram of the fiber at each preparation stage during the preparation of the manganese-based fiber catalytic material in Example 1 of the present invention.

[0044] Depend on Figure 3It can be seen that APANF presents three weight loss platforms. The first weight loss platform is caused by the desorption of water and gas adsorbed on the fiber surface. This platform lasts until about 150 °C. The second weight loss platform is caused by the removal of nitrogen-containing groups. The third weight loss platform is caused by the degradation of the fiber polymer main chain. The second weight loss platform of TAPANF after thermal oxidation is significantly weakened, and the initial weight loss temperature of the third weight loss platform is also slightly shifted back, indicating that the structure of nitrogen-containing groups becomes more stable during thermal oxidation pretreatment, which improves the thermal stability of the fiber. After manganese oxide loading, MnO x / TAPANF, the second weight loss platform remained basically unchanged, but the weight loss endpoint temperature shifted backward, indicating that the loading of manganese oxide improved the thermal stability of the fiber; MnO x After the third weight loss platform of TAPANF, the residual weight of the fiber increased significantly, which was caused by the loading of inorganic manganese oxide. oo -MnO x The first weight loss platform of / TAPANF fiber was significantly weakened, and the second weight loss platform remained basically unchanged, indicating that ozone activation further improved the thermal stability of the fiber.

[0045] Embodiment 2: A method for preparing a manganese-based fiber catalytic material, specifically comprising: The commercial acrylic fiber was washed three times with deionized water and dried at 60°C to constant weight. 400 mL of diethylenetriamine solution (the mass fraction of diethylenetriamine in the diethylenetriamine solution was 20%, and the solvent of the diethylenetriamine solution was ethylene glycol) was added to a three-necked flask, and then 2 g of pretreated acrylic fiber was immersed in the diethylenetriamine solution at 80°C for 4 hours, and then heated to 130°C for 5 hours, cooled, washed, and dried at 60°C to constant weight to obtain amino fiber. The exchange capacity was measured to be 4.05mmol / g; 2g of the prepared amino fiber was placed in a tube furnace, air was introduced into the tube furnace at 100mL / min for 30min, then the temperature was raised to 250℃ at 20℃ / min and kept constant for 0.5h, cooled, sealed and stored to obtain pre-oxidized amino fiber; 1g of pre-oxidized amino fiber was placed in a conical flask containing 200mL of 20mmol / L potassium permanganate solution, and the reaction was carried out at 10℃ constant temperature for 12h, taken out, washed with water until the eluate was colorless, and dried at 60℃ to constant weight to obtain a manganese-based fiber catalytic material precursor; the manganese-based fiber catalytic material precursor was placed in an ozone gas flow with an ozone concentration of 30mg / L, a mass space velocity of 960000mL / (g·h), and a temperature of 120℃ for in-situ activation for 2h to obtain a manganese-based fiber catalytic material. After testing, the manganese content in the manganese-based fiber catalytic material was 145.1 mg / g.

[0046] The manganese-based fiber catalytic material and the manganese-based fiber catalytic material precursor prepared in this embodiment were used to catalyze the ozone oxidation degradation of benzene in the gas; the degradation experimental conditions were: space velocity 120000 mL / (g·h), reaction temperature 90°C, benzene concentration in the gas 100 ppm, ozone concentration 4.0-4.5 mg / L, and gas humidity 0-10%. After the degradation reaction was completed, the benzene content in the gas was detected and the benzene removal rate was calculated.

[0047] It was found through testing that the removal rate of benzene in the gas by the manganese-based fiber catalytic material prepared in this embodiment was 99.2%, and the selectivity of inorganic carbon oxides in the product was 98.5%; while the removal rate of benzene in the gas by the manganese-based fiber catalytic material precursor was 65%. This shows that the catalytic performance of the manganese-based fiber catalytic material prepared by the present invention is significantly higher than that of the manganese-based fiber catalytic material precursor that has not been treated with ozone in-situ activation, and can be used to catalyze ozone oxidation to degrade benzene pollutants in the gas.

[0048] Embodiment 3: A method for preparing a manganese-based fiber catalytic material, specifically comprising: The commercial acrylic fiber was washed three times with deionized water and dried at 60°C to constant weight. 40 mL of ethylenediamine solution (the mass fraction of ethylenediamine in the ethylenediamine solution is 40%, and the solvent of the ethylenediamine solution is propylene glycol) was added to a three-necked flask, and then 2 g of pretreated acrylic fiber was weighed and immersed in the ethylenediamine solution at 60°C for swelling for 12 hours, and then heated to 100°C for reaction for 12 hours, cooled, washed, and dried at 60°C to constant weight to obtain amino fiber, and its exchange capacity was measured to be 3.06 mmol / g; 1 g of the obtained amino fiber was immersed in a tubular furnace, and air was passed into the tubular furnace at 500 mL / min. The mixture was weighed for 30 minutes, then heated to 220°C at 2°C / min and kept at this temperature for 2 hours, cooled, and sealed to obtain pre-oxidized amine-based fibers; 1g of pre-oxidized amine-based fibers was placed in a conical flask containing 100mL of a 50mmol / L potassium permanganate solution, and oscillated at 25°C for 6 hours, then taken out, washed with water until the eluate was colorless, and dried at 60°C to constant weight to obtain a manganese-based polymer fiber catalytic material precursor; the manganese-based polymer fiber catalytic material precursor was placed in an ozone gas flow with an ozone concentration of 10mg / L, a mass space velocity of 480000 mL / (g·h), and a temperature of 115°C for in-situ activation for 6 hours to obtain a manganese-based fiber catalytic material. After testing, the manganese content in the manganese-based fiber catalytic material was 105.2mg / g.

[0049] The manganese-based fiber catalytic material and the manganese-based fiber catalytic material precursor prepared in this embodiment were used to catalyze the ozone oxidation degradation of toluene in the gas; the toluene degradation experimental conditions were: space velocity 120000 mL / (g·h), reaction temperature 100°C, toluene concentration in the gas 90 ppm, ozone concentration 4.0-4.5 mg / L, and gas humidity 0-10%. After the degradation reaction was completed, the toluene content in the gas was detected and the toluene removal rate was calculated.

[0050] It was found through testing that the manganese-based fiber catalytic material prepared in this embodiment has a removal rate of 100% for toluene in the gas, and the selectivity of inorganic carbon oxides in the product is greater than 99%; while the removal rate of toluene in the gas by the manganese-based fiber catalytic material precursor is 67%. This shows that the catalytic performance of the manganese-based fiber catalytic material prepared in the present invention is significantly higher than that of the manganese-based fiber catalytic material precursor that has not been treated with ozone in-situ activation, and can be used to catalyze ozone oxidation to degrade toluene pollutants in the gas.

[0051] Example 4: Study on the effect of ozone in-situ activation treatment time on the catalytic performance of the prepared manganese-based fiber catalytic material: In order to study the effect of ozone in-situ activation treatment time on the catalytic performance of the prepared manganese-based fiber catalyst material, the manganese-based fiber catalyst material precursor prepared in Example 1 was placed in an ozone gas flow with an ozone concentration of 20 mg / L, a mass space velocity of 1200000 mL / (g·h) and a temperature of 110°C for ozone in-situ activation treatment for different times. Then, the manganese-based fiber catalyst materials obtained after different ozone in-situ activation times were used to catalyze the ozone oxidation and degradation of toluene in the gas. The experimental conditions for toluene degradation were: the mass space velocity was 9.6×10 5 mL / (g·h), reaction temperature is 110℃, toluene concentration in the gas is 100ppm, ozone concentration is 1000ppm, and gas humidity is 0-10%. After the degradation reaction is completed, the toluene content in the gas is detected and the toluene removal rate is calculated. The results are as follows Figure 4 shown.

[0052] Depend on Figure 4 It can be seen that in the first 180 minutes of the ozone in-situ activation treatment process, when the manganese-based fiber catalyst material catalytically degraded toluene in the gas, the toluene removal efficiency quickly increased from 0.20 to 0.63, and the catalytic activity increased by more than 2 times, indicating that the ozone activation process can significantly improve the catalytic activity of the fiber catalyst material; and when the ozone in-situ activation treatment time is from 180min to 420min, the toluene removal efficiency has no obvious improvement. Therefore, the ozone in-situ activation treatment time is preferably 180 min.

[0053] Finally, it should be noted that the above embodiments are only preferred embodiments of the present invention, and are not intended to limit the present invention in other forms. Any technician familiar with the profession may use the above technical content as inspiration to make changes or modifications. This is an equivalent embodiment of equivalent changes. However, any simple modification, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the technical concept of the present invention still fall within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a manganese-based fiber catalytic material, characterized in that: The polymer fiber is subjected to a pre-oxidation treatment to obtain a pre-oxidized polymer fiber; the pre-oxidized polymer fiber is subjected to an in-situ oxidation treatment using potassium permanganate in-situ oxidation method to obtain a manganese-based polymer fiber catalytic material precursor; the manganese-based polymer fiber catalytic material precursor is subjected to an ozone in-situ activation treatment using an ozone gas flow to obtain a manganese-based fiber catalytic material.

2. The preparation method according to claim 1, characterized in that The temperature of the ozone in-situ activation treatment is 110-130° C., and the time is 2-8 hours; the concentration of ozone in the ozone gas flow is 10-40 mg / L, and the mass space velocity of the ozone gas flow during the ozone in-situ activation treatment is 240000-1200000 mL / (g·h).

3. The preparation method according to claim 2, characterized in that: The specific operation of in-situ oxidation of the pre-oxidized polymer fiber by potassium permanganate in-situ oxidation method is as follows: adding the pre-oxidized polymer fiber to potassium permanganate solution for oxidation reaction, collecting the polymer fiber after the reaction is completed, and washing and drying the polymer fiber to obtain a manganese-based polymer fiber catalytic material precursor.

4. The preparation method according to claim 3, characterized in that The concentration of the potassium permanganate solution is 20-100 mmol / L, the liquid-solid ratio of the potassium permanganate solution to the pre-oxidized polymer fiber is (20-200) mL:1 g, the temperature of the oxidation reaction is 10-40° C., and the time of the oxidation reaction is 0.5-12 h.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The pre-oxidation treatment is specifically: heat treating the polymer fiber in an oxygen-containing gas; the heat treatment temperature is 200-250° C., the heat treatment time is 0.5-4 h; the flow rate of the oxygen-containing gas is 100-500 mL / min.

6. The preparation method according to claim 5, characterized in that: The polymer fiber is acrylic fiber or modified acrylic fiber; the modified acrylic fiber is acrylic fiber grafted with amino groups, and the amino groups are grafted on the acrylic fiber through the reaction of polyamine compounds and -CN groups in the acrylic fiber.

7. A manganese-based fiber catalytic material prepared by the preparation method according to any one of claims 1 to 6.

8. The manganese-based fiber catalytic material according to claim 7, characterized in that: The manganese-based fiber catalytic material is in the form of one or more of fiber, wool, needle-punched cloth, and knitted cloth.

9. Use of the manganese-based fiber catalytic material according to claim 7 or 8 in a catalyst.

10. The use according to claim 9, characterized in that: The catalyst includes a catalyst in an ozone oxidation process; the ozone oxidation includes ozone oxidation degradation of benzene series in a gas phase; the benzene series includes toluene and / or benzene; and the degradation temperature is 70-110°C.

Citation Information

Patent Citations

  • Arsenic adsorbing fiber and synthesizing method thereof

    CN101569854A

  • Manganese dioxide nano catalytic membrane for catalyzing ozone to degrade organic wastewater and preparation method thereof

    CN111617759A

  • Ozone and formaldehyde-benzene co-catalytic degradation catalyst and preparation method and application thereof

    CN112569928A

  • In-situ activation fixed-bed heterogeneous catalyst reactor

    CN113509891A

  • Manganese-loaded fiber catalyst for catalytic ozonation as well as preparation method and application of manganese-loaded fiber catalyst

    CN114405546A